1963
DOI: 10.1021/jf60126a001
|View full text |Cite
|
Sign up to set email alerts
|

Chelation in Nutrition, Chelation as a Basic Biological Mechanism

Abstract: The reaction of metal ions and organic ligands provides a buffer system for concentration of metal ion in the medium. Modification of the ligand by intermediary metabolism or metabolic alterations in pH may selectively vary the metal ion concentration. Application of these principles to the problems of iron absorption, cobalt metabolism, and the growth of microorganisms is described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1964
1964
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…The chelate reaction mechanism of EDTA-LiCoO 2 milling is shown below: It has been reported that metal chelates are cyclic structure of metal atoms and organic ligand formed by donation of electrons from the ligand donor atoms, usually oxygen, nitrogen, or sulfur is the electron acceptor metal ion. The chemical bond formed in this manner may vary in characteristics from the covalent to the almost completely ionic type (Rubin and Princiotto, 1963). EDTA, which is an aminopolycarboxylic acid containing six ligands, two amines and four carboxyl groups, can coordinate with metal ions at the molar ratio of 1:1.…”
Section: Reaction Mechanism Of Licoo 2 With Edta During Ball Millingmentioning
confidence: 99%
“…The chelate reaction mechanism of EDTA-LiCoO 2 milling is shown below: It has been reported that metal chelates are cyclic structure of metal atoms and organic ligand formed by donation of electrons from the ligand donor atoms, usually oxygen, nitrogen, or sulfur is the electron acceptor metal ion. The chemical bond formed in this manner may vary in characteristics from the covalent to the almost completely ionic type (Rubin and Princiotto, 1963). EDTA, which is an aminopolycarboxylic acid containing six ligands, two amines and four carboxyl groups, can coordinate with metal ions at the molar ratio of 1:1.…”
Section: Reaction Mechanism Of Licoo 2 With Edta During Ball Millingmentioning
confidence: 99%
“…A convenient measure of this value is the log KMA (15). For transferrin and ferric ion, log KMA has been variously reported as approximately 27 (16), 27.7 for the first iron atom of transferrin, and 29 or 30.2 for the second iron atom of the molecule (17,18).…”
Section: Discussionmentioning
confidence: 99%